Pengembangan Bahan Ajar Interaktif Berbasis Microsoft Powerpoint Tema 9 Subtema 2 Kelas V SD Negeri 13 Pontianak Barat - Kiki Rizki Efriani; Kartono Kartono; Siti Halidjah (Journal on Education, 2024)
The aim of the study was to develop interactive teaching materials based on Microsoft PowerPoint for class V with 9 sub-themes 2 themes. The research uses a development model adapted from the Thiagarajan design model, namely the 4D (four-D) model which includes three steps, namely stage (1) Define, stage (2) Design, and stage (2) Develop. The source of the research data was obtained from the fifth grade teacher at Public Elementary School 13 West Pontianak. The research data is in the form of a questionnaire (questionnaire) and interviews conducted during the initial observation. The data analysis technique used is Purwanto. Implementation of research to test the feasibility of interactive teaching materials based on Microsoft PowerPowint. The feasibility level of interactive teaching material products from the material aspect average percentage of 97.7% which has valid criteria and from the media aspect the average percentage is 87.7% which has valid criteria. Constraints in the development of interactive teaching materials include the lack of school facilities. In addition, the obstacle in this research is the limited time to develop interactive teaching materials